Enamel and dental anomalies in latent‐transforming growth factor beta‐binding protein 3 mutant mice. (February 2017) - Morkmued, Supawich; Hemmerle, Joseph; Mathieu, Eric; Laugel‐Haushalter, Virginie; Dabovic, Branka; Rifkin, Daniel B.; Dollé, Pascal; Niederreither, Karen; Bloch‐Zupan, Agnès
Abstract : Latent‐transforming growth factor beta‐binding protein 3 (LTBP‐3) is important for craniofacial morphogenesis and hard tissue mineralization, as it is essential for activation of transforming growth factor‐ β (TGF‐ β ). To investigate the role of LTBP‐3 in tooth formation we performed micro‐computed tomography (micro‐CT), histology, and scanning electron microscopy analyses of adult Ltbp3‐/‐ mice. The Ltbp3‐/‐ mutants presented with unique craniofacial malformations and reductions in enamel formation that began at the matrix formation stage. Organization of maturation‐stage ameloblasts was severely disrupted. The lateral side of the incisor was affected most. Reduced enamel mineralization, modification of the enamel prism pattern, and enamel nodules were observed throughout the incisors, as revealed by scanning electron microscopy. Molar roots had internal irregular bulbous‐like formations. The cementum thickness was reduced, and microscopic dentinal tubules showed minor nanostructural changes. Thus, LTBP‐3 is required for ameloblast differentiation and for the formation of decussating enamel prisms, to prevent enamel nodule formation, and for proper root morphogenesis. Also, and consistent with the role of TGF‐ β signaling during mineralization, almost all craniofacial bone components were affected in Ltbp3‐/‐ mice, especially those involving the upper jaw and snout. This mouse model demonstrates phenotypic overlap with Verloes Bourguignon syndrome, also caused by mutation of LTBP3, which is hallmarked by craniofacial anomalies and amelogenesis imperfecta phenotypes.